Pengenalan Wajah Untuk Sistem Kehadiran Menggunakan Metode Eigenface dan Euclidean Distance - Fahmi Syuhada; I Gede Pasek Suta Wijaya; Fitri Bimantoro (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
he development of Information Technology allows faces that are one part of identity that has been widely be used as biometric based security system. This research is a process of designing and making of identification system which is able to detect of human attended. This system implements: viola-jones, eigenface and euclidean distance methods. Viola-jones method is employed as face detection. Eigenface method is used to reduce the face image and to get the weight value. The euclidean distance is impemented as a classification method. The accuracy of this system against 30 register subjects and 15 unregistered subjects is 84%. This accuracy is obtained after the addition of preprocessing process and adaptive training model on the system. Therefore, this research concluded that viola-jones method is very good as face detection, however need to be added face correction process. Meanwhile, eigenface and euclidean distance methods provide good results to recognize face when many training faces are given. The more variations faces of subject are, the higher accuracy is given.